Pengaruh Kredibilitas Endorser terhadap Online Purchase Intention dengan Brand Awareness sebagai Pemediasi pada Situs Belanja Online Tokopedia: Penelitian - Intan Candradewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Marketing is a crucial part of a company. If marketing in a company runs well, it will have an impact on increasing demand. A very important element in marketing activities is communication. Communication can inform consumers about products or services that can create a purchasing process. Brand awareness or brand awareness is the ability of a brand to appear in the minds of consumers when they are thinking about a particular product and how easy the brand is. The purpose of this study is to determine the influence of endorser credibility on online purchase intention with brand awareness as a mediator. The research location is in Tabanan City using a purposive sampling technique. The respondents used were 110 respondents. The data analysis technique used was Path Analysis. Based on the analysis, the research results showed that brand awareness has a positive and significant effect on purchase intention. Celebrity endorsers have a positive and significant effect on brand awareness. Celebrity endorsers have a positive and significant effect on purchase intention. Brand awareness is able to mediate the influence of celebrity endorsers on purchase intention.